APPLICATION OF A PRIORI ALGORITHM FOR BOOK RECOMMENDATION (CASE STUDY: MEDAN CITY LIBRARY AND ARCHIVES OFFICE) - Mey Shinta, Clara; Kelana Jaya, Indra; Fatmaira, Zira (Journal of Mathematics and Technology (MATECH), 2023)
Libraries are institutions that collect printed and recorded knowledge. Books can be borrowed from the library for a duration according to library regulations. Based on the results of observations that the placement of book layouts carried out at the Library and Archives Service was arranged into bookshelves based on categories where each category was given a certain number. The Library and Archives Service has not provided any information to recommend books that are often borrowed by visitors based on the level of frequency of reading or borrowing books. By utilizing library lending data, information can be extracted about what books visitors often borrow and the relationship between each book. Problems that often occur in the relationship between book titles, authors, publishers and the year of the book need to be analyzed based on books that are often borrowed as service recommendations to visitors as well as arrangement adjustments according to borrower's needs. In the above problem, we need an action or solution that can be used to solve the problem above by implementing data mining using the association rule method to determine the relationship between books in the library. From the results of tests carried out on a sample of 30 data obtained, it can be concluded that the results of the Final Association Rules have a support value of 30% and 100% confidence. So the guards can recommend the book JB5 (sharia cooperative), with the author PN1 (Hery, S.E, M .Si), published (P4) by Gramedia Widiasarana Indonesia, with the year of publication (THN2), namely 2016-2020.